(untitled) (Colloquium Agrariae. ISSN: 1809-8215, 2020)
This study aimed to analyze and compare the agronomic characteristics and development of the root system by means of image processing of different cultivars of tropical grasses of the genera Brachiaria and Panicum. The experiment carried out at the experimental station of the Research, Rural extension and land regularization company of Paraiba – EMPAER in Alagoinha - PB, in a rainfed agriculture system. In June 2019 to 45 days after sowing, the grasses were cut for aerial part evaluation: biomass composition, forage yield, root system: volume and surface area of the cultivars Mombaça, Tamani, Zuri, Massai, Piatã and Ipyporã. There was a difference between cultivars for all variables analyzed, except for the leaf: stem ratio. The cv. Mombaça was the one that presented the best agronomic and root results, being the one that best adapted the edaphoclimatic conditions of the region, in contrast to Ipyporã was the least expressive for forage yield and water efficiency. These aerial characteristics and their relationship with root diagnosis are of great importance for choosing the cultivar that best suits certain environmental conditions at the time of cultivation.